Visuospatial Working Memory Capacity in the Brain After Working Memory Training in College Students With ADHD: A Randomized Controlled Trial. Issue 7 (May 2021) - Woltering, Steven; Gu, Chao; Liu, Zhong-Xu; Tannock, Rosemary
Objective: ADHD has been associated with persistent problems of working memory. This study investigated the efficacy of an intensive and adaptive computerized working memory treatment (CWMT) at behavioral and neural levels.Method: College students ( n = 89; 40 females) with ADHD were randomized into a standard-length CWMT (45 min/session, 25 sessions, n = 29), shortened-length CWMT (15 min/session, 25 sessions, n = 32), and a waitlist group ( n = 28). Both CWMT groups received treatment for 5 days a week for 5 weeks. Lab sessions before and after CWMT assessed electroencephalography (EEG) indicators of working memory, behavioral indicators of working memory performance, and ADHD symptomatology.Results: No evidence was found for neural or any other behavioral transfer effects of improvement for the CWMT treatment groups over the active control or waitlist group.Conclusion: Our study does not provide evidence for the benefits of CWMT at neural or behavioral levels.